Energy balance, nitrogen balance, and growth in preterm infants fed expressed breast milk, a premature infant formula, and two low-solute adapted formulae. Issue 12 (December 1982) - Brooke, O G; Wood, C; Barley, J
Abstract : Energy balance, nitrogen balance, and growth studies were done in 37 preterm infants (20 of very low birthweight) who were fed on expressed breast milk or on one of 3 formulae each of different composition, including a special premature formula and a highly adapted 'humanised' formula. The variability of breast milk composition was such that it would have been difficult to predict the infants' protein and energy intakes under normal nursing conditions. All measured parameters of nutritional performance were best in infants fed on the 'premature' formula and were reflected in greater weight gain, linear growth, and head growth. The nitrogen balance data suggest that the highly adapted formula, which had a protein content comparable with that of mature human milk, contained too little protein for small preterm infants.